An Analysis of the Effected Factors on Communication Breakdown on Speaking - Jala, Alexandra Loesia D. (JELP Journal of English Language and Pedagogy, 2025)
Communication breakdown in speaking performance has become a significant issue among English as a Foreign Language (EFL) learners, particularly affecting their oral fluency. This research aims to analyze the factors contributing to communication breakdown, focusing on interpersonal skills and language learning environments. A qualitative approach was employed, utilizing semi-structured interviews with 35 students from SMAN 1 Kalisat to gather insights about their speaking experiences. The key findings reveal that linguistic challenges, interpersonal skills, classroom environment, and preferred learning styles significantly impacts students’ communication breakdowns. Students reported that fear of judgment and lack of preparation as major causes of their speaking difficulties. This research highlights the importance of understanding these factors to improve students’ oral fluency and communication effectiveness. The findings provide valuable recommendations for educators to foster a supportive learning atmosphere and enhance teaching strategies that cater to diverse learning preferences.